Formal preparation of regioregular and alternating thiophene–thiophene copolymers bearing different substituents - Mori, Atsunori; Fujita, Keisuke; Kubota, Chihiro; Suzuki, Toyoko; Okano, Kentaro; Matsumoto, Takuya; Nishino, Takashi; Horie, Masaki (Beilstein Journal of Organic Chemistry, 2020)
Differently substituted thiophene–thiophene-alternating copolymers were formally synthesized employing a halo-bithiophene as a monomer. Nickel-catalyzed polymerization of bithiophene with substituents at the 3-position, including alkyl-, fluoroalkyl-, or oligosiloxane-containing groups, afforded the corresponding copolymers in good to excellent yield. The solubility test in organic solvents was performed to reveal that several copolymers showed a superior solubility. X-ray diffraction analysis of the thin film of the alternating copolymers composed of methyl and branched oligosiloxane substituents was also performed, and the results suggested the formation of a dual-layered film structure.
Keywords: alternating copolymer; nickel(II) catalyst; oligosiloxane; regioregular polythiophene; solubility

(untitled) - Sirringhaus, H.; Tessler, N.; Friend, R. H. (Science, 1998)

(untitled) - Li, G.; Shrotriya, V.; Huang, J.; Yao, Y.; Moriarty, T.; Emery, K.; Yang, Y. (Nat. Mater., 2005)

(untitled) - Osaka, I.; McCullough, R. D. (Acc. Chem. Res., 2008)

(untitled) - Bao, Z.; Dodabalapur, A.; Lovinger, A. J. (Appl. Phys. Lett., 1996)

(untitled) - Yokozawa, T.; Ohta, Y. (Chem. Rev., 2016)

(untitled) - Okamoto, K.; Luscombe, C. K. (Polym. Chem., 2011)

(untitled) - Krasovskiy, A.; Krasovskaya, V.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Tamba, S.; Shono, K.; Sugie, A.; Mori, A. (J. Am. Chem. Soc., 2011)

(untitled) - Tamba, S.; Tanaka, S.; Okubo, Y.; Meguro, H.; Okamoto, S.; Mori, A. (Chem. Lett., 2011)

(untitled) - Matsubara, K.; Ueno, K.; Shibata, Y. (Organometallics, 2006)

(untitled) - Herrmann, W. A. (Angew. Chem., Int. Ed., 2002)

(untitled) - Fujita, K.; Sumino, Y.; Ide, K.; Tamba, S.; Shono, K.; Shen, J.; Nishino, T.; Mori, A.; Yasuda, T. (Macromolecules, 2016)

(untitled) - Mori, A.; Ide, K.; Tamba, S.; Tsuji, S.; Toyomori, Y.; Yasuda, T. (Chem. Lett., 2014)

(untitled) - Ogura, T.; Kubota, C.; Suzuki, T.; Okano, K.; Tanaka, N.; Matsumoto, T.; Nishino, T.; Mori, A.; Okita, T.; Funahashi, M. (Chem. Lett., 2019)

(untitled) - Noh, S.; Gobalasingham, N. S.; Thompson, B. C. (Macromolecules, 2016)

(untitled) - Locke, J. R.; McNeil, A. J. (Macromolecules, 2010)

(untitled) - Palermo, E. F.; Darling, S. B.; McNeil, A. J. (J. Mater. Chem. C, 2014)

(untitled) - Lee, E.; Hammer, B.; Kim, J.-K.; Page, Z.; Emrick, T.; Hayward, R. C. (J. Am. Chem. Soc., 2011)

(untitled) - Ouhib, F.; Desbief, S.; Lazzaroni, R.; De Winter, J.; Gerbaux, P.; Jérôme, C.; Detrembleur, C. (Macromolecules, 2012)

(untitled) - Hong, X. M.; Tyson, J. C.; Collard, D. M. (Macromolecules, 2000)

(untitled) - Bjørnholm, T.; Greve, D. R.; Reitzel, N.; Hassenkam, T.; Kjaer, K.; Howes, P. B.; Larsen, N. B.; Bøgelund, J.; Jayaraman, M.; Ewbank, P. C.; McCullough, R. D. (J. Am. Chem. Soc., 1998)

(untitled) - Reitzel, N.; Greve, D. R.; Kjaer, K.; Howes, P. B.; Jayaraman, M.; Savoy, S.; McCullough, R. D.; McDevitt, J. T.; Bjørnholm, T. (J. Am. Chem. Soc., 2000)

(untitled) - Smith, Z. C.; Meyer, D. M.; Simon, M. G.; Staii, C.; Shukla, D.; Thomas, S. W., III (Macromolecules, 2015)

(untitled) - Nakamura, K.; Tamba, S.; Sugie, A.; Mori, A. (Chem. Lett., 2013)

(untitled) - Fujita, K.; Nakagawa, N.; Sunahara, K.; Ogura, T.; Okano, K.; Mori, A. (Synthesis, 2017)

(untitled) - Kantchev, E. A. B.; O'Brien, C. J.; Organ, M. G. (Angew. Chem., Int. Ed., 2007)

(untitled) - Sun, D.; Li, Y.; Ren, Z.; Bryce, M. R.; Li, H.; Yan, S. (Chem. Sci., 2014)

(untitled) - Nakagawa, N.; Ogura, T.; Fujita, K.; Sumino, Y.; Hashimoto, T.; Okano, K.; Mori, A. (Chem. Lett., 2017)

(untitled) - Shen, J.; Fujita, K.; Matsumoto, T.; Hongo, C.; Misaki, M.; Ishida, K.; Mori, A.; Nishino, T. (Macromol. Chem. Phys., 2017)

(untitled) - Matsumoto, T.; Nishi, K.; Tamba, S.; Kotera, M.; Hongo, C.; Mori, A.; Nishino, T. (Polymer, 2017)

(untitled) - Inoue, R.; Yamaguchi, M.; Murakami, Y.; Okano, K.; Mori, A. (ACS Omega, 2018)